(untitled) (Journal of the Bangladesh Agricultural University, 2017)
Crop allelopathy may be useful to minimize serious problems in the present agricultural production such as environmental pollution, unsafe production, human health concerns, depletion of crop diversity, soil sickness and reduction of crop productivity. In this phenomenon an experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh to evaluate the effect of crop residues of mustard on weed management and crop performance of T. aman rice. The experiment consisted of three cultivars of T. aman rice viz., BR11, BR23 and BRRI dhan49 and five different level of mustard crop residues such as no crop residues, mustard crop residues @ 0.5, 1.0, 1.5 and 2.0 t ha–1. The experiment was laid out in a randomized complete block design with three replications. Five weed species belonging to three families infested the experimental plots. Weed population, weed dry weight and percent inhibition of weed were significantly influenced by mustard crop residues and cultivar. The maximum weed growth was noticed with the cultivar BR23 and the minimum was found in the cultivar BR11. The grain yield as well as the other yield contributing characters produced by BR11 was the highest among the studied varieties. The highest percent inhibition of 71.17, 69.19, 80.88, 70.48 and 86.97 was in Shama (Echinochlo acrusgalli), Panishapla (Nymphaea nouchali), Panichaise (Scirpus juncoides), Panikachu (Monochoria vaginalis) and Susnishak (Marsilea quadrifolia), respectively which was caused by the application of mustard crop residues @ 2 t ha–1. The highest loss of grain yield was obtained where no crop residues were incorporated. The highest numbers of tillers hill-1, numbers of grains panicle–1, 1000-grain weight, grain yield, straw yield were observed where mustard crop residues were incorporated @ 2.0 t ha–1. BR11 cultivar with all treatments produced the highest grain and straw yield among the treatment combination. The results of this study indicate that different amount of mustard crop residues showed potential activity to suppress weed growth. J. Bangladesh Agril. Univ. 15(2): 133-139, December 2017